Combining Satellite and Terrestrial Interferometric Radar Data to Investigate Surface Displacement in the Storfjord and Kåfjord Area, Northern Norway. - Eriksen, Harald Øverli (UiT Norges arktiske universitet, 2017)
Due to their all-weather all-day capabilities and increased availability, synthetic aperture radar (SAR) interferometric displacement datasets have gained popularity in a variety of scientific disciplines. Both satellite and ground-based platforms are used. Satellite-based radar instruments cover large areas on a regular basis without the need for in-situ instrumentation. As with all measuring techniques, radar has its limitations. One intrinsic property is its ability to only observe displacement along the Line-Of-Sight (LOS) direction, thus displacement components diverging from the LOS-direction are underestimated, which limits interpretation of displacement processes. Being portable, the LOS-direction of ground-based radars can be selected. However, as with the satellite-based instruments, ground-based radars still suffer from underestimation of displacement that arises due to divergence from the instrument’s LOS-direction. In this project, we have combined multi-geometrical radar datasets from ground- and satellite-based radar to form two-dimensional (2D) and three-dimensional (3D) surface displacement vectors, creating new ways to interpret surface deformation. By plotting the resulting 2D and 3D surface displacement vector datasets in map and cross-sections, we interpret displacement at the landform- and landscape-scale. Using 2D surface displacement vectors produced from scenes acquired by the TerraSAR-X satellite in ascending and descending orbits we have studied rockslides, rock glaciers and solifluction lobes at the landform scale. In addition, we have investigated the use of periglacial landform-specific displacement rates as a tool for geomorphological mapping at the landscape-scale. By also including data from ground-based radar we have calculated 3D surface displacement vectors for the Jettan rockslide. In contrast with single radar datasets, using 2D and 3D surface displacement vectors together with topography enables us to calculate different kinematic diagnostic parameters that can be used as ...